PREVALENCE OF MALNUTRITION AMONG UNDER FIVE-YEAR-OLD CHILDREN IN A RURAL COMMUNITY OF NELLANAD PANCHAYAT, KERALA - Dr. Jithu S J Nath; Dr. Jyothi M V (Journal of Population Therapeutics and Clinical Pharmacology, 2025)
Malnutrition is an important global issue, with India having one of the highest prevalence rates of malnourished children worldwide. Nearly 35% of children under 5 years old in India are suffering from malnutrition. Indicating the need for tackling malnutrition.Aim: The study is focused on determining the prevalence of malnutrition among children under five years old in Nellanad Panchayath, Kerala, and identifying the relationship between maternal factors, neonatal implications, dietary habits, and the presence of undernourishment children in the same community.Materials and Methods: Data was collected from the community using the cluster sampling method through house-to-house visits and interviews using a structured questionnaire among the 100 identified participants.Results: The study revealed that 11% had grade 1 protein-energy malnutrition (PEM), 4% had grade 2 PEM, and 2% had grade 3 PEM indicating a notable association between antenatal complications and malnutrition, as evidenced by a statistically significant p-value of 0.018.Conclusion: Poverty, poor food access, insufficient healthcare facilities, and socioeconomic inequities contribute to malnutrition among children in India. Awareness about malnutrition alongside poverty reduction, healthcare access, maternal and child care, and nutrition education is needed for effective malnutrition-reduction through government, non-profit, and community collaboration.